Pemanfaatan Pendekatan User-Centered Design dan Komunikasi Pembangunan dalam Pengembangan Aplikasi Clean Earth untuk Pengelolaan Sampah Cerdas - Sukmasetya, Pristi; Dwihantoro, Prihatin (Universitas Muhammadiyah Metro, 2025)
Waste management remains a complex environmental issue in Indonesia that requires an interdisciplinary approach. This study aims to design and develop the Clean Earth application as a digital solution for community-based waste management by integrating the User-Centered Design (UCD) approach with Participatory Development Communication principles. A qualitative-descriptive method was employed through field observations, user interviews, interface prototyping, and limited user testing. The Clean Earth app consists of three core features: GoPah (scheduled waste collection), Barter (digital waste-bank system), and Education (interactive learning media on waste utilization). The System Usability Scale (SUS) evaluation involving 25 respondents yielded an average score of 84.6, categorized as Excellent Usability. Moreover, the Education feature effectively enhanced public awareness and understanding of sustainable waste practices. The findings demonstrate that integrating information technology with development communication can create a digital medium that is both functional and participatory, fostering behavioral change toward environmental responsibility. This study contributes to the formulation of an adaptive and inclusive Smart Circular Waste Management model applicable to various local community contexts in Indonesia.